GESTION DE RIESGO Y EVENTOS ADVERSOS EN CIRUGIA TORACICA (Revista Argentina de Cirugía, 2022)
Introduction: An adverse event occurs as a result of factors and phenomena conjugated for his appearance (poorly developed processes, poorly applied technologies, inadequate infrastructure or failed human interactions) triggering an incident that can cause injury, disability, morbidity, length prolongation of hospitalization, death, arising from health care and not the underlying disease.Objectives: Identify, analyze and report preventable adverse events that occurred in surgical clinic processes in thoracic surgery as risk prevention. Recognize and analyze factors of adverse events. Encourage continuous education to develop a safety culture.Design: Retrospective, observational statistical study.Materials and methods: a retrospective statistical analysis of adverse events (EA) in thoracic surgery from a General Surgery service, analyzing contributing factors of a total 57 patients of thoracic surgery from December 01 2009 to January 01, 2011.Results: 10 (17.5 %) patients presented EA and all (100 %) were considered preventable. There were temporary disability in 5 cases (50 %) and 4 (40 %) there was no disabilities added to the pathology of base. One (10 %) introduced permanent disability. Mortality associated with the adverse event not occurred. The 100 % of the EA occurred by human factors, 7 (70 %) by inadequate technique, 1 (10 %) by fault in diagnostic procedure,2 (20 %) by complications in postoperative management.Conclusions: When an adverse event occurs, it failed the health system. The checklist is useful and can alert and avoid unsafe actions.
Keywords: surgery; adverse event; prevention